2018
DOI: 10.1016/j.trsl.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of innervation by encapsulated adipocytes with engineered vitamin A metabolism

Abstract: Innervation is a fundamental basis for function and survival of tissues. In the peripheral tissues, degenerative diseases create a neurotoxic metabolic milieu that either causes neurodegeneration or fails to sustain regenerative growth and reinnervation of injured/diseased tissues. Encapsulation of cells producing neurotrophic factors can augment axon growth and neuron survival; however, sustained innervation in vivo requires a combination of factors promoting axon growth and guidance pathway that are released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…The mechanism by which EREG could contribute to energy expenditure state remains unknown, since EREG was not able to induce direct thermogenic responses in preadipocytes (Kir, White, Kleiner, Kazak, Cohen, Baracos & Spiegelman 2014). However, thermogenic modifications in adipocytes deficient in aldehyde dehydrogenase a1 were accompanied by Ereg expression (Shen, Yasmeen, Marbourg, Xu, Yu, Fadda, Flechtner, Lee, Popovich & Ziouzenkova 2018). Here we test EREG efficacy in the induction of LEP secretion, in vivo and in vitro, and the relevance of this secretion for the induction of catabolic energy expenditure states.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which EREG could contribute to energy expenditure state remains unknown, since EREG was not able to induce direct thermogenic responses in preadipocytes (Kir, White, Kleiner, Kazak, Cohen, Baracos & Spiegelman 2014). However, thermogenic modifications in adipocytes deficient in aldehyde dehydrogenase a1 were accompanied by Ereg expression (Shen, Yasmeen, Marbourg, Xu, Yu, Fadda, Flechtner, Lee, Popovich & Ziouzenkova 2018). Here we test EREG efficacy in the induction of LEP secretion, in vivo and in vitro, and the relevance of this secretion for the induction of catabolic energy expenditure states.…”
Section: Introductionmentioning
confidence: 99%
“…Some research showed that ALDH1A1 could transform precursor retinaldehydes into retinoic acid receptor (RAR) which was a kind of steroid hormone receptor ( Kiefer et al, 2012 ). Interestingly, deficiency of the ALDH1A1 gene also limited the formation of RAR ( Shen et al, 2018 ). Besides, Hammond et al (2001) demonstrated that antagonists of retinoic acid receptors (RARs) effectively inhibited the growth prostate carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that perhaps EphB2 forward signaling is important for the inhibition of adipogenesis by MSC. Moreover, Eph-ephrin communication has been reported in white adipose tissue, where ephrin-A4 and ephrin-A5 were found to be a downstream signaling pathway to aldehyde dehydrogenase, which stimulates the development and innervation of white adipose tissue (Shen et al, 2018 ). Also, ephrin-B1 was identified to be down-regulated in mature adipocytes of obese mice and shown to suppress the adipose inflammatory response (Mori et al, 2013 ).…”
Section: The Role Of Eph-ephrin Signaling Within the Mesenchymal Linementioning
confidence: 99%